Une approche syntaxique et lexicale des verbes pronominaux - Petersilka, Corina (Studia Romanica Posnaniensia, 2012)
This Construction grammar approach to French refl exive verbs describes the formal and semantic constraints at work in the different refl exive constructions, points out at their different branches of inheritance and shows cases of fusion with other argument structures. The article suggests a family tree of French reflexive constructions which appear to be derived from different transitive constructions. It also deals with how the reflexive argument structure modifies the semantics of the transitive verb used in reflexive construction.